Tautan Politik Dalam Wacana Revisi Undang-Undang Penanggulangan Bencana di Ruang Politik Digital - Sapto Setyo Nugroho; Agus Priyanto; Amir Syamsuadi; Fadli Afriandi (Jayapangus Press, 2026)
Despite the critical urgency of revising the Disaster Management Law after two decades of implementation, this policy reform has not been formally executed by the Parliament. This paper aims to analyze disaster governance through a political linkage approach to examine the political dimensions of disaster policy systematically. Using an interpretive qualitative method with digital discourse analysis, this study examines data sourced from YouTube webinar content involving the Parliament, Civil Society Organizations (CSOs), academics, practitioners, and the private sector. The research findings summarize various strategic policy reform proposals, encompassing aspects of institutional strengthening, mandatory budget allocation policies, the integration of Disaster Risk Analysis documents, and the reinforcement of social inclusiveness and local knowledge. The main contribution of this paper highlights the dominance of technocratic linkage within the relationship between CSOs and Parliament in the digital political space. This interaction demonstrates a slight shift from procedural democracy toward substantive democracy, focusing heavily on policy content depth and programmatic problem-solving.